Waterfowl Censuses on the Mississippi River from St. Louis, Missouri, to Cairo, Illinois: 6 December 1973 through 2 April 1974 - Bellrose, Frank C.; Sanderson, Glen C.; Crompton, Robert (1974)
not peer reviewed Open Restriction set for Item 123043 on 2022-04-12T19:29:01Z with date null by braxton@illinois.edu. Submitted by Susan Braxton (braxton@illinois.edu) on 2022-04-12T19:34:32Z No. of bitstreams: 1 WaterfowlCensusesMississippi19731974.pdf: 7613706 bytes, checksum: 0909113bca8ff0845956c1fa5582fbf3 (MD5) Made available in DSpace on 2022-04-12T19:34:32Z (GMT). No. of bitstreams: 1 WaterfowlCensusesMississippi19731974.pdf: 7613706 bytes, checksum: 0909113bca8ff0845956c1fa5582fbf3 (MD5) Previous issue date: 1974-08-06 unpublished Open